PENGARUH PEMBELAJARAN PROBING-PROMPTING BERBASIS PROBLEM POSING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA MTS AL-MUNAWWAROH BANGKO - Anita, Febri; Susanti, Ade; Ferinaldi, Ferinaldi (STKIP YPM Bangko, 2018)
This research of background overhador by understanding of mathematical concept use model study of probing-prompting based problem posing better than the understanding of mathematical concept use conventional study of class student of VIII MTs Al-Munawwaroh Bangko year 2016/2017. This research type is research of experiment with population 90 people. Technique withrawal of sampel use sampling random simple. Chosen sampel is class of VIII A/Pa as experiment class and class of VIII B/Pa as class of kontrol. Technique collecting tes of is understanding of mathematical concept which in form of problem of essay at cube items and log. Technique analyse data used to test hypothesis is test-t of data analysis of tes final experiment class obtained by ean 39,24 varians 49,85, while control class obtained by mean 32,88, varians 43,17. Result of hypothesis test obtained, thitung = 2,79 and ttabel = 1,68 because thitung > ttabelof hense Ho refused and Ha accepted. Conclusoin of this research that is understanding of mathematical concept use study of probing better than the understanding of concept use convensional study of class student of VIII MTs Al-Munawwaroh Bangko year 2016/2017.